PENGARUH RETURN ON EQUITY, LEVERAGE, DAN LIKUIDITAS TERHADAP KESULITAN KEUANGAN - Gunawan, Yohandy; Trisnawati, Estralita (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to determine the effect of return on equity, leverage and liquidity on financial distress in non-financial companies listed on the Indonesia Stock Exchange during 2017 -2020. The sample was selected using the purposive sampling method and the valid data were 62 companies. The data processing technique used multiple regression analysis assisted by EViews 12 for windows released 2020 and Microsoft Excel 2016. The results of this study indicate that liquidity has a significant effect on the company's financial distress, while return on equity and leverage have no effect on corporate financial distress. The implications of this research are the need for processing the company's current assets properly to be able to reduce the risk of experiencing financial distress.